1998
DOI: 10.1103/physrevlett.81.2052
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Laser Cooling of a Fast Stored Ion Beam through Dispersive Coupling

Abstract: Transverse laser cooling of a fast stored Be-9(+) ion beam based on a single-particle force independent of the ion density is demonstrated at the Heidelberg Test Storage Ring. The cooling scheme exploits longitudinal-horizontal coupling through ring dispersion and the transverse intensity profile of the longitudinally merged laser beam. By linear betatron coupling the horizontal force is extended to the vertical degree of freedom resulting in true 3D laser cooling. The observed transverse-cooling mechanism rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 18 publications
(20 reference statements)
1
23
0
Order By: Relevance
“…would be strongly suppressed, and the beam heating by laser-induced diffusion could become dominant. The loss of transverse cooling would be more critical vertically, since the horizontal motion would still be cooled by dispersive cooling [4]. The observed decrease of the horizontal beam size after the blowup starts supports this hypothesis as the IBS calculation indicated heating (which before the blowup is countered by the dispersive cooling).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…would be strongly suppressed, and the beam heating by laser-induced diffusion could become dominant. The loss of transverse cooling would be more critical vertically, since the horizontal motion would still be cooled by dispersive cooling [4]. The observed decrease of the horizontal beam size after the blowup starts supports this hypothesis as the IBS calculation indicated heating (which before the blowup is countered by the dispersive cooling).…”
supporting
confidence: 71%
“…We argue that this low-current vertical blowup of the beam arises due to a sudden reduction of the indirect transverse cooling mediated by intrabeam scattering (IBS), which thus no longer compensates the diffusive heating caused by the spontaneous emission of photons during laser cooling. The horizontal dimension, however, is cooled by the dispersive coupling between the horizontal and the longitudinal dimensions [4] and thus does not blow up. Our results indicate that there may be serious limitations to the possibility of using laser cooling in the creation of a crystalline beam.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The powerful longitudinal cooling effect is effectively transferred through these coupling sources under the resonance conditions and we can thus expect efficient, indirect laser cooling in both transverse directions. Lauer et al have demonstrated another indirect transverse cooling scheme based on a dispersive transverse cooling force caused by horizontal displacement of a cooling laser [13]. This scheme, however, has a practical limitation that the laser power is not fully utilized for beam cooling because of a poor overlap between the laser and ions.…”
Section: Introductionmentioning
confidence: 99%
“…This offers great perspectives for future facilities that will provide high-quality stored ion beams for precision experiments. Laser cooling of stored coasting and bunched ion beams has been demonstrated at the TSR in Heidelberg (Germany) [2,3], and at ASTRID in Aarhus (Denmark) [4]. At the Experimental Storage Ring (ESR) in Darmstadt (Germany), first laser cooling experiments at moderately relativistic energies were conducted [5].…”
Section: Introductionmentioning
confidence: 99%